Communication—Design of Heated Cells for In Situ Absorption and Reflectance UV–Vis Spectroelectrochemistry. Issue 6 (1st June 2022) - Khan, Fariha; Kowalchik, Tim; Nelson, Tanner; Atnip, Aaron; Johnson, Johnathan; Young, Jeremiah; Siri, Connor; Dallon, Adam; Warren, Roseanne
Abstract : Spectroelectrochemistry (SEC) enables in-operando UV–vis study of electrochemical cells to explore the evolution of different cell components and understand cell mechanisms. Researchers have demonstrated various custom UV–vis cell designs to accommodate SEC experiments. However, existing designs do not easily permit temperature ramp techniques to examine the effects of rapidly changing cell temperature or high temperature conditions on cell mechanisms. This communication presents two easy-to-replicate, low-cost cell designs that are incorporable with existing UV–vis systems (transmittance, reflectance) and enable high temperature, rapid heating SEC experiments. Each cell design was tested to evaluate temperature ramp and sealing performance.